Analisis Semiotika Roland Barthes Pada Iklan Rokok Apache Versi Hidup Gue Cara Gue - Yeyen Nurimba; Amir Muhiddin (Journal of Communication Sciences (JCoS), 2020)
One of the media products that have the ability to change people’s knowledge, attitudes and behavior is advertising. Advertising is a form of communication between producers, consumers and audiences by utilizing mass media, so that messages can be accepted by audiences globally and simultaneously. The advertising communication contains information about the existence of the product through words, images, writing and voice which are packaged in such an attractive way to encourage audiences to purchase the advertised products. This study aims to analyze and raise the meaning of the signifier, signified, denotative and connotative as well as the moral messages contained in the Apache cigarette advertisement version of My Life, My Way, which is broadcast on television media. Lifting a story about the success story of man in his coffee making business. To examine this problem thoroughly and deeply, a qualitative descriptive approach and Roland Barthes’ semiotic analysis were used. Semiotics is considered appropriate to find out or decipher something that is behind the sign meaning of the advertisement. In this study, it is concluded that the meaning of the signifier, signified, denotative and connotative is listed in several signs such as coffe, humans, NTT areas, facial expressions and unyielding efforts. The moral message that is conveyed is that it takes a resilient and unyielding nature when trying to achieve success, trusting in our abilities as a support to improve our lives for the better and be grateful for whatever results we get because of the good and bad things that happen to us is something that has been arranged by Allah SWT.